A surface multi-element composite plating method for a conductor of a trolley line of a copper-based alloy

CN122979986APending Publication Date: 2026-10-27YANGZHOU TIANHAI SLIDING LINE ELECTRIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611452892.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

本发明对铜基合金滑触线导体的工作表面进行镀前预处理,在形成的活性铜基表面依次设置金属过渡层和导电支撑层,并采用碳化硅颗粒和石墨颗粒添加质量比例逐级增加的复合镀液组进行连续复合镀覆,使颗粒供给差异按照复合镀覆顺序转移至梯度多元复合工作层的厚度方向。由此,铜基合金基体、金属过渡层、导电支撑层和梯度多元复合工作层依次连接,梯度多元复合工作层靠近导电支撑层的一侧保持较高比例的连续金属相,朝向滑动工作表面的区域逐渐增加碳化硅颗粒和石墨颗粒的共沉积水平,使载流、承载耐磨和滑动润滑所需的材料状态沿镀层厚度方向进行配置,在保持导电路径的同时降低滑动过程中发生机械犁削、局部塑性变形和过大剪切阻力的程度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979986A_ABST
    Figure CN122979986A_ABST
Patent Text Reader

Abstract

The application discloses a surface multi-element composite plating method of a copper-based alloy trolley conductor and belongs to the technical field of alloy surface treatment. The method comprises the following steps: performing pre-plating treatment on the working surface of the copper-based alloy trolley conductor to form an active copper-based surface; sequentially forming a metal transition layer and a conductive support layer to obtain a composite plating base body; configuring a first composite plating solution, a second composite plating solution and a third composite plating solution with gradually increased adding mass proportions of silicon carbide particles and graphite particles respectively; continuously performing composite plating on the composite plating base body according to the arrangement order of the three kinds of composite plating solutions, maintaining the circulating and dispersing state of each composite plating solution, and forming a gradient multi-element composite working layer; and performing post-plating treatment on the gradient composite plating conductor to obtain the surface multi-element composite plating copper-based alloy trolley conductor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of alloy surface treatment technology, specifically relating to a multi-component composite plating method for the surface of a copper-based alloy sliding contact wire conductor. Background Technology

[0002] Copper-based alloy sliding contact wire conductors are used to transmit current to moving power-receiving components in a relative sliding state. During current carrying, the working surface simultaneously withstands contact pressure and continuous sliding friction. Copper-based alloys have high conductivity, but the frictional wear state of the working surface affects the sliding contact and current carrying process. Therefore, a silver layer or a silver-based composite coating containing solid particles is typically formed on the surface of the copper or copper alloy substrate. The silver phase undertakes the conductivity and sliding contact function, and co-deposited particles are used to adjust the frictional wear state of the working surface.

[0003] When composite electroplating is performed using a composite plating solution with a single particle ratio, the particle supply state received by the silver deposition interface during the coating growth process is basically consistent, resulting in a relatively uniform particle composition along the thickness direction of the composite coating. Increasing the particle content will cause the continuous silver phase to be separated by more particle interfaces, while decreasing the particle content will reduce the number of particles that can participate in load-bearing and lubrication in the sliding working surface. Therefore, it is difficult to form the material states required for continuous current carrying, compositional transition, and wear resistance and friction reduction in different thickness regions of the same composite coating.

[0004] The number and distribution of carbon particles entering the silver matrix are also affected by the particle surface state and the dispersion and suspension state of the composite plating solution. During continuous composite electroplating, when particles settle, agglomerate, or undergo local concentration changes, the number of particles reaching the silver deposition interface changes with the processing location and processing time, causing fluctuations in the number and distribution of particles in the composite coating, and further affecting the silver phase connection state, sliding contact state, and wear process. Summary of the Invention

[0005] This invention overcomes the shortcomings of the prior art and provides a method for multi-component composite plating of the surface of a copper-based alloy sliding contact wire conductor.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a method for surface multi-element composite plating of a copper-based alloy sliding contact wire conductor, comprising the following steps: S1: Pre-treatment of the working surface of the copper-based alloy sliding contact line conductor before plating is performed to form an active copper-based surface; S2: A metal transition layer and a conductive support layer are sequentially formed on the surface of an active copper substrate to obtain a composite plating substrate; S3: Configure the first composite plating solution, the second composite plating solution and the third composite plating solution, so that the mass ratio of silicon carbide particles and graphite particles added in each composite plating solution increases step by step from the first composite plating solution to the third composite plating solution, to obtain a composite plating solution group. S4: Using a composite plating solution group, the composite plating substrate is continuously composite plating in the order of the first composite plating solution to the third composite plating solution, and the circulation and dispersion state of each composite plating solution is maintained to form a gradient multi-element composite working layer and obtain a gradient composite plating conductor. S5: Perform post-plating treatment on the gradient composite plated conductor to obtain a copper-based alloy sliding contact conductor with multi-component composite plating on the surface.

[0007] Preferably, the metal transition layer is a nickel transition layer continuously covering the surface of the active copper substrate, and the conductive support layer is a silver conductive support layer continuously covering the nickel transition layer and free of silicon carbide particles and graphite particles; the gradient multi-component composite working layer includes a first composite layer segment, a second composite layer segment, and a third composite layer segment formed sequentially outward from the silver conductive support layer. The silver conductive support layer and the three composite layer segments adopt a continuously grown silver matrix, and the co-deposition level of silicon carbide particles and graphite particles in the three composite layer segments increases progressively in the order of the first composite layer segment, the second composite layer segment, and the third composite layer segment.

[0008] Preferably, after the first composite layer is formed and after the second composite layer is formed, a clean, oil-free gas is used to form a non-contact airflow that acts laterally on the working surface to remove the composite plating solution carried on the surface of the corresponding composite layer that can flow or drip, return the detached composite plating solution to the corresponding original composite plating solution tank, and keep a continuous wet liquid film on the surface of the corresponding composite layer.

[0009] Preferably, the respective mass ratio of silicon carbide particles and graphite particles is characterized by the mass concentration of the corresponding particles in the corresponding composite plating solution; let the mass concentrations of silicon carbide particles in the first composite plating solution, the second composite plating solution, and the third composite plating solution be respectively. , and The mass concentrations of graphite particles added were as follows: , and Particle size distribution gradient coefficient for: Particle size distribution gradient coefficient It ranges from 1.9 to 2.4.

[0010] Preferably, the mass concentration of silicon carbide particles in the first composite plating solution is 3.0 g / L, and the mass concentration of graphite particles is 1.0 g / L; the mass concentration of silicon carbide particles in the second composite plating solution is 5.7-7.2 g / L, and the mass concentration of graphite particles is 1.9-2.4 g / L; the mass concentration of silicon carbide particles in the third composite plating solution is 10.8-17.3 g / L, and the mass concentration of graphite particles is 3.6-5.8 g / L. The particle concentrations in the second and third composite plating solutions are determined according to the same particle ratio gradient coefficient K, and the mass ratio of silicon carbide particles to graphite particles in all three composite plating solutions is 3:1.

[0011] Preferably, the first composite plating solution, the second composite plating solution, and the third composite plating solution are respectively set in independent composite plating solution tanks, and are respectively output from the corresponding composite plating solution tank and returned to the original composite plating solution tank through independent circulation pipelines; all three composite plating solutions use non-cyanide sulfite-based silver plating solutions, and the silver ion concentration, free sulfite concentration, and pH in the three composite plating solutions are respectively set with the same target values, wherein the silver ion concentration is 20-40 g / L, the free sulfite concentration is 80-160 g / L, and the pH is 8.0-9.5. The independent circulation pipelines are not equipped with fine filter components to intercept silicon carbide particles and graphite particles.

[0012] Preferably, the average particle size of silicon carbide particles is 0.3-1.5 μm, and the average particle size of graphite particles is 0.5-2.0 μm. Silicon carbide particles and graphite particles are added to their respective aqueous dispersion media, and a nonionic dispersant is added at a dosage of 0.5%-2.0% of the corresponding particle mass. The media are then mechanically stirred and ultrasonically dispersed for 15-40 minutes to form a silicon carbide particle dispersion with a particle mass concentration of 80-150 g / L and a graphite particle dispersion with a particle mass concentration of 50-100 g / L. The corresponding base silver plating solution is circulated, and the silicon carbide particle dispersion is fed into the mixing zone of the circulating plating solution. After further circulation and mixing, the graphite particle dispersion is then fed into the mixing zone.

[0013] Preferably, the thickness of the first composite layer accounts for 25%-40% of the total thickness of the gradient multi-element composite working layer, the thickness of the second composite layer accounts for 30%-40% of the total thickness of the gradient multi-element composite working layer, and the thickness of the third composite layer accounts for 25%-40% of the total thickness of the gradient multi-element composite working layer. The sum of the thicknesses of the three composite layers is 100%, and the total thickness of the gradient multi-element composite working layer is 10-25 μm. The plating temperature for forming the three composite layers is 25-40℃, and the cathode current density is 0.5-2.0 A / dm³. 2 Furthermore, the silver ion concentration, free sulfite concentration, pH, and plating temperature in the three composite plating stages all adopted the same target values.

[0014] Preferably, nickel electrodeposition is performed on a moistened active copper-based surface, using a nickel plating bath with a nickel ion concentration of 50-100 g / L, a pH of 3.5-4.8, a temperature of 40-60°C, and a cathode current density of 1.0-4.0 A / dm³. 2 A nickel transition layer with a thickness of 0.5-2.0 μm is formed. Silver electrodeposition is performed on the surface of the nickel transition layer using a non-cyanide sulfite silver electroplating system. The silver plating solution used has a silver ion concentration of 20-40 g / L, a free sulfite concentration of 80-160 g / L, a pH of 8.0-9.5, a temperature of 25-40℃, and a cathode current density of 0.5-2.0 A / dm³. 2 This forms a silver conductive support layer with a thickness of 3-8 μm.

[0015] Preferably, the pretreatment before plating is carried out in the order of degreasing, water washing, micro-etching, water washing, and activation. Specifically, the working surface is continuously degreased for 1-5 minutes using an alkaline degreasing solution at a temperature of 40-65℃. The working surface after water washing is continuously micro-etched using a sulfuric acid-hydrogen peroxide micro-etching system. The sulfuric acid concentration in the sulfuric acid-hydrogen peroxide micro-etching system is 50-120 g / L, the hydrogen peroxide concentration is 15-40 g / L, the micro-etching temperature is 20-35℃, the micro-etching time is 20-90 s, and the micro-etching depth is 0.3-1.5 μm. The working surface after micro-etching and water washing is activated using a sulfuric acid aqueous solution with a concentration of 30-80 g / L. The activation temperature is 15-30℃, the activation time is 15-60 s, and after activation, the activation solution carried on the working surface is replaced with flowing water to keep the active copper base surface continuously moist.

[0016] This invention addresses the shortcomings of the prior art and has the following beneficial effects: This invention pre-treats the working surface of a copper-based alloy sliding contact wire conductor before plating. A metal transition layer and a conductive support layer are sequentially deposited on the formed active copper base surface. A composite plating solution with progressively increasing mass ratios of silicon carbide and graphite particles is used for continuous composite plating, transferring the particle supply difference along the thickness direction of the gradient multi-element composite working layer according to the composite plating sequence. Thus, the copper-based alloy substrate, metal transition layer, conductive support layer, and gradient multi-element composite working layer are sequentially connected. The side of the gradient multi-element composite working layer closest to the conductive support layer maintains a higher proportion of continuous metal phase, while the co-deposition level of silicon carbide and graphite particles gradually increases towards the sliding working surface. This ensures that the material state required for current carrying, wear resistance, and sliding lubrication is configured along the plating thickness direction, maintaining the conductive path while reducing the degree of mechanical plowing, localized plastic deformation, and excessive shear resistance during sliding.

[0017] This invention progressively increases the mass ratio of silicon carbide and graphite particles in the first, second, and third composite plating solutions, and continuously composite plating the substrate in the order of the first to the third composite plating solutions. This results in low-particle-supply, medium-particle-supply, and high-particle-supply states in the three composite plating stages, respectively, thereby progressively increasing the co-deposition level of the two types of particles in the first, second, and third composite layers. The first composite layer retains a high proportion of continuous silver phase, the second composite layer accommodates changes in particle composition, and the third composite layer forms relatively more silicon carbide particle bearing positions and graphite particle lubrication contact areas. The silicon carbide particles restrict the silver matrix from mechanical plowing and local plastic deformation under contact loads, while the graphite particles are gradually exposed during sliding and wear, reducing the shear resistance of the contact area. When further using a particle ratio gradient coefficient to limit the incremental relationship between the two types of particles in adjacent composite plating solutions, the two types of particles change in association according to the same incremental degree, reducing the mismatch between the supply of wear-resistant particles and the supply of lubricating particles, as well as the deviation of the working layer state caused by insufficient particle gradient or local enrichment of particles.

[0018] This invention maintains the circulating dispersion state of the first, second, and third composite plating solutions during continuous composite plating, ensuring that silicon carbide and graphite particles are continuously transported to the silver deposition interface along with their respective composite plating solutions, reducing particle sedimentation, agglomeration, and fluctuations in particle supply to the plating area. Furthermore, by employing independent composite plating tanks and circulation pipelines, the three composite plating solutions circulate and return to their original tanks, making the particle supply state independent for each composite plating stage. Between adjacent composite plating stages, the composite plating solution carried on the surface of the formed composite layer and capable of flowing or dripping is removed, and the detached solution is returned to its corresponding original tank, reducing particle dilution caused by the entry of the previous stage's solution into the next. After liquid control, the surface of the composite layer retains a continuous wet liquid film and can directly enter the next composite plating stage without intermediate water washing and drying. This allows the silver matrix of the subsequent composite layer to continue growing from the continuous silver phase on the surface of the previous composite layer, reducing deposition interruptions and interlayer discontinuities caused by surface drying, salt residue, or re-oxidation. This reduces the fluctuation of particle composition along the conductor length of the gradient multi-component composite working layer and maintains the continuous bonding state between adjacent composite layers.

[0019] The composite plating solution group with progressively increasing particle mass ratios determines the direction of particle composition variation along the thickness of the gradient multi-element composite working layer. Circulating dispersion and inter-stage liquid control limit the shift in particle supply state of each composite plating solution during continuous plating. Wet transfer ensures that the particle composition variation and continuous silver matrix growth are maintained simultaneously. The metal transition layer and conductive support layer further provide the interface and current-carrying basis for continuous composite plating. Thus, the pre-formed particle ratio differences in the composite plating solution can be stably transferred to the corresponding composite layer segments in a predetermined order, forming an inner continuous silver phase, an intermediate compositional transition, and an outer wear-resistant and friction-reducing particle configuration. This avoids situations where only particle composition differences are formed without continuous current carrying capacity and interlayer bonding, or where the plating process is only stabilized without forming a functional configuration along the thickness direction. Attached Figure Description

[0020] Other features, objects, and advantages of the invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 This is a flowchart of a multi-component composite plating method for the surface of copper-based alloy sliding contact wire conductors. Detailed Implementation

[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] like Figure 1 As shown, a method for multi-element composite plating of a copper-based alloy sliding contact wire conductor includes the following steps: S1: Pre-treatment of the working surface of the copper-based alloy sliding contact line conductor before plating is performed to form an active copper-based surface; S2: A metal transition layer and a conductive support layer are sequentially formed on the surface of an active copper substrate to obtain a composite plating substrate; S3: Configure the first composite plating solution, the second composite plating solution and the third composite plating solution, so that the mass ratio of silicon carbide particles and graphite particles added in each composite plating solution increases step by step from the first composite plating solution to the third composite plating solution, to obtain a composite plating solution group. S4: Using a composite plating solution group, the composite plating substrate is continuously composite plating in the order of the first composite plating solution to the third composite plating solution, and the circulation and dispersion state of each composite plating solution is maintained to form a gradient multi-element composite working layer and obtain a gradient composite plating conductor. S5: Perform post-plating treatment on the gradient composite plated conductor to obtain a copper-based alloy sliding contact conductor with multi-component composite plating on the surface.

[0023] The following description, in conjunction with the specific implementation process of each step, further explains the method so that those skilled in the art can clearly understand the interrelationship of each step in implementation and the resulting technical results.

[0024] In step S1, the working surface of the copper-based alloy sliding contact wire conductor may be adhered to by processing grease, organic contaminants, and oxides, and may contain an unstable shallow layer affected by processing, resulting in inconsistent wetting states and metal deposition initiation states at different length locations. Pre-treatment of the working surface is performed to remove surface substances that hinder metal deposition and expose the copper-based material, forming an active copper-based surface capable of continuously accepting metal deposition.

[0025] Specifically, for the working surface of the copper-based alloy sliding contact wire conductor that requires the formation of a composite coating, pretreatment is carried out in the following order: degreasing, water washing, micro-etching, water washing, and activation. Degreasing and corresponding water washing remove grease, organic contaminants, and degreasing solution residue, creating a clean surface that can be continuously wetted by the aqueous treatment solution; micro-etching and corresponding water washing remove oxides, processing residues, and dissolution products, continuously exposing the newly formed copper-based material; activation removes the thin oxide layer formed during water washing and transfer, and keeps the working surface moist.

[0026] In the specific implementation process, an alkaline degreasing solution suitable for copper and copper alloys is used to continuously degrease the working surface. The alkaline components in the degreasing solution saponify saponifiable greases, while the surfactant components wet, emulsify, and disperse non-saponifiable greases and other organic contaminants, causing the contaminants adhering to the working surface to detach from the copper-based alloy material. The temperature of the degreasing solution is controlled at 40-65℃, and the degreasing time is controlled at 1-5 minutes. During continuous processing, the effective length of the degreasing area is matched with the passing speed of the copper-based alloy sliding contact line conductor, ensuring that any length position on the working surface receives the corresponding degreasing time.

[0027] After degreasing, a continuous water rinse is performed to remove the degreasing solution, emulsified contaminants, and detached solid impurities from the working surface. The rinsing is completed when there is no visible oil film, foam, or degreasing solution residue on the working surface, and the water can spread continuously across the surface. This rinsing results in a clean copper-based surface that can continuously contact the acidic micro-etching solution.

[0028] A sulfuric acid-hydrogen peroxide micro-etching system was used to continuously micro-etch clean copper-based surfaces. The sulfuric acid concentration was controlled at 50-120 g / L, the hydrogen peroxide concentration at 15-40 g / L, the micro-etching temperature at 20-35℃, the micro-etching time at 20-90 s, and the micro-etching depth at 0.3-1.5 μm. Hydrogen peroxide oxidizes the copper and copper alloy components on the working surface, while the sulfuric acid introduces the corresponding oxidation products into the micro-etching solution, thereby continuously removing the original oxides, processing residues, and unstable shallow materials affected by processing. When the micro-etching depth reaches 0.3-1.5 μm, it allows for continuous exposure of the newly formed copper-based material and reduces the differences in the original surface condition at different length locations, while limiting the dimensional changes and localized roughening of the working surface caused by excessive micro-etching.

[0029] After micro-etching, residual sulfuric acid, hydrogen peroxide, copper ions, and other dissolved products are removed using flowing water. The washed surface maintains a continuous water film, forming a new copper-based surface. The new copper-based surface is then activated using a 30-80 g / L sulfuric acid aqueous solution, with the activation temperature controlled at 15-30℃ and the activation time controlled at 15-60 seconds. The sulfuric acid solution removes the thin oxide layer formed on the new copper-based surface during washing and transport, restoring the copper alloy material to its directly exposed state. After activation, the activating solution carried on the working surface is replaced with flowing water. This replacement keeps the working surface continuously wet, preventing localized drying that could lead to re-oxidation or salt residue. This results in an active copper-based surface that can be continuously wetted by the metal plating solution and accept metal nucleation and deposition.

[0030] In step S2, the active copper-based surface can accept metal deposition, but there are differences in material composition, hardness, and interfacial diffusion state between the copper-based alloy substrate and the silver-based composite working layer. Directly forming the silver-based composite working layer can easily cause the differences in the substrate surface to be transmitted to the outer working layer. It is necessary to sequentially form a metal transition layer and a conductive support layer on the active copper-based surface to establish a continuous interfacial transition structure and current-carrying structure between the copper-based alloy substrate and the subsequent gradient multi-element composite working layer.

[0031] In this step, a moistened active copper-based surface is used as the direct deposition surface, and nickel electrodeposition and silver electrodeposition are performed sequentially. Nickel ions are reduced on the active copper-based surface to form a continuously covering nickel transition layer, creating a metallic transition interface between the copper-based alloy matrix and the silver layer, and restricting the diffusion of copper components into the outer silver layer. Silver ions are reduced on the surface of the nickel transition layer to form a silver conductive support layer free of silicon carbide and graphite particles, resulting in a continuous silver phase across the entire working surface.

[0032] In practice, the copper-based alloy sliding contact wire conductor is kept in a cathode conductive state while the active copper-based surface is immersed in a nickel plating bath. The nickel plating bath uses soluble nickel salts to provide nickel ions, with the nickel ion concentration controlled at 50-100 g / L, the pH of the plating bath controlled at 3.5-4.8, the temperature of the plating bath controlled at 40-60℃, and the cathode current density controlled at 1.0-4.0 A / dm³. 2 Nickel ions gain electrons on the active copper-based surface and are reduced to metallic nickel. The resulting nickel crystal nuclei continue to grow and connect with each other during the electrodeposition process, transforming the working surface from an exposed state of copper-based material to a state of continuous coverage by metallic nickel.

[0033] The nickel transition layer thickness is controlled between 0.5 and 2.0 μm, with continuous coverage of the active copper substrate surface as the completion condition. A thickness of 0.5 μm or more reduces localized copper exposure and forms a continuous interface; a thickness controlled within 2.0 μm limits internal stress and processing time. The continuous nickel phase provides a relatively uniform metallic surface for subsequent silver deposition and forms a diffusion barrier region between the copper-based alloy substrate and the silver conductive support layer. After nickel electrodeposition, flowing water is used to replace the acidic nickel plating solution carried on the surface, preventing the acidic solution from entering the subsequent silver plating solution and altering its pH and complexation state.

[0034] Using a nickel transition layer as the deposition surface, silver electrodeposition was performed using a non-cyanide sulfite silver electroplating system. The silver ion concentration was controlled at 20-40 g / L, the free sulfite concentration at 80-160 g / L, the pH of the plating bath at 8.0-9.5, the plating bath temperature at 25-40℃, and the cathode current density at 0.5-2.0 A / dm³. 2 Sulfite forms a soluble complex with silver ions, enabling continuous nucleation and growth of silver on the surface of the nickel transition layer. Adjacent silver deposition areas gradually connect and cover the nickel transition layer, forming a silver conductive support layer with a thickness of 3-8 μm.

[0035] During the formation of the silver conductive support layer, no silicon carbide or graphite particles are added, allowing the silver deposition areas to be continuously connected by metallic silver. When the thickness of the silver conductive support layer reaches 3 μm or more, it can continuously cover the nickel transition layer and form a stable current-carrying region; when the thickness is controlled within 8 μm, the outer thickness space is used to form a gradient multi-element composite working layer. Both the silver conductive support layer and the subsequent gradient multi-element composite working layer use silver as a continuous metal matrix, allowing the silver matrix formed by subsequent composite electrodeposition to continue growing from the surface of the silver conductive support layer. After the silver conductive support layer reaches the target thickness, the silver plating solution that can continuously flow on the surface is removed while keeping the silver conductive support layer wet, resulting in a composite plating substrate.

[0036] In step S3, the composite working layer formed by the composite plating solution with a single particle ratio has a basically uniform particle composition in the thickness direction, making it difficult to separately form a continuous current-carrying region near the silver conductive support layer, a transitional region in the middle, and a wear-resistant and friction-reducing region on the outside. Therefore, a first composite plating solution, a second composite plating solution, and a third composite plating solution are prepared using a non-cyanite-based silver plating solution with the same composition. The mass concentration of silicon carbide particles and graphite particles is increased stepwise in the order of the first composite plating solution, the second composite plating solution, and the third composite plating solution, forming a composite plating solution group with low particle supply state, medium particle supply state, and high particle supply state.

[0037] Specifically, three independent composite plating baths are set up, and non-cyanide sulfite base silver plating solutions are added to each of the three baths. The silver ion concentration in the base silver plating solution is controlled at 20-40 g / L, the free sulfite concentration at 80-160 g / L, and the pH at 8.0-9.5. The three composite plating baths in the same composite plating bath group use the same target values ​​for silver ion concentration, free sulfite concentration, and pH, so that the compositional differences between the three composite plating solutions are concentrated in the mass concentration of silicon carbide particles and graphite particles added.

[0038] When preparing the basic silver plating solution, dissolve the sulfite complex component in water, and add silver salt or silver complex solution while keeping the solution flowing, allowing silver ions to enter the sulfite complex system. After adding the silver salt or silver complex solution, add water to the target volume, and adjust the silver ion concentration, free sulfite concentration, and pH to the corresponding ranges. Continuously circulate the prepared basic silver plating solution until the silver salt and sulfite complex component are completely dissolved, and the silver ion concentration, free sulfite concentration, and pH remain consistent at different sampling locations.

[0039] Silicon carbide particles with an average particle size of 0.3-1.5 μm were selected as wear-resistant particles, and graphite particles with an average particle size of 0.5-2.0 μm were selected as lubricating particles. Both silicon carbide and graphite particles were pre-wetted using an aqueous dispersion medium compatible with the base silver plating solution. The two types of particles were then added to their respective aqueous dispersion media, along with a nonionic dispersant at a concentration of 0.5%-2.0% of the corresponding particle mass.

[0040] Silicon carbide and graphite particles were mechanically stirred and ultrasonically dispersed for 15-40 minutes respectively to wet the particles with the aqueous dispersion medium and dissociate loose agglomerates. The dispersion treatment was completed when no visible dry powder or large agglomerates were found in the dispersion, and no rapid stratification occurred during a short settling period after the forced dispersion was stopped. The particle mass concentration of the silicon carbide dispersion was controlled at 80-150 g / L, and that of the graphite dispersion was controlled at 50-100 g / L. After the dispersion treatment was completed, the silicon carbide and graphite particle dispersions were slowly circulated.

[0041] The particle addition mass concentration refers to the actual mass of target particles added per unit volume of the composite plating solution when preparing the composite plating solution, expressed in g / L. The addition amounts of silicon carbide particle dispersion and graphite particle dispersion are calculated based on the actual mass of silicon carbide particles and graphite particles contained in the dispersion, respectively. Aqueous dispersion media and nonionic dispersants are not included in the particle addition mass.

[0042] Using particle size distribution gradient coefficient A unified characterization is used to assess the increasing mass concentration of silicon carbide and graphite particles in adjacent composite plating solutions. Let... , and The mass concentrations of silicon carbide particles added to the first, second, and third composite plating solutions are respectively set as follows: , and The particle ratio gradient coefficient is calculated by adding different mass concentrations of graphite particles to the first, second, and third composite plating solutions, respectively. satisfy: .

[0043] Particle size distribution gradient coefficient The concentration of silicon carbide particles added to the first composite plating solution should be controlled at 1.9-2.4. The graphite particle addition concentration was set at 3.0 g / L. The concentration was set at 1.0 g / L. The particle concentrations in the second and third composite plating solutions were determined according to the following relationships: , , , .

[0044] According to the particle size gradient coefficient Calculated to a concentration of 1.9-2.4, and retaining the particle addition concentration to 0.1 g / L, the particle addition concentration in the second composite plating solution is 5.7-7.2 g / L for silicon carbide and 1.9-2.4 g / L for graphite; the particle addition concentration in the third composite plating solution is 10.8-17.3 g / L for silicon carbide and 3.6-5.8 g / L for graphite. The particle addition concentrations in the second and third composite plating solutions follow the same particle ratio gradient coefficient. The correlation is determined, and the particles are not selected independently within their respective ranges. Therefore, the mass ratio of silicon carbide particles to graphite particles in the three composite plating solutions is maintained at 3:1, and the mass concentration of both types of particles increases stepwise according to the same particle ratio gradient coefficient.

[0045] When adding the particle dispersion to the corresponding base silver plating solution, the base silver plating solution is kept circulating, and the silicon carbide particle dispersion is continuously fed into the mixing zone of the circulating plating solution. After the silicon carbide particle dispersion has been added and circulated for mixing, the graphite particle dispersion is fed into the corresponding mixing zone in the same manner. The first composite plating solution, the second composite plating solution, and the third composite plating solution use the same particle addition sequence, and the particle dispersion is not concentrated in the static area of ​​the composite plating solution tank.

[0046] After the silicon carbide particle dispersion and graphite particle dispersion were added, the silver ion concentration, free sulfite concentration, and pH in the three composite plating baths were measured. When the addition of the particle dispersion caused changes in the concentration of the base components, an adjusting solution with the same composition as the base silver plating solution was used to restore the silver ion concentration, free sulfite concentration, and pH in the three composite plating baths to the same target values.

[0047] The first, second, and third composite plating solutions continuously circulate within their respective composite plating tanks and independent circulation pipelines. The composite plating solutions are output from their respective tanks, pass through a mixing zone, and return to their original tanks. The circulation flow is controlled by conditions including the absence of a continuous particle deposit layer at the bottom of the composite plating tanks, the absence of visible large agglomerates in the main composite plating solution, and the absence of large areas of floating particles on the surface. Extensive air entrapment and the formation of stable foam in the composite plating solution are also limited. The circulation pipelines do not contain fine filters capable of trapping the silicon carbide and graphite particles used.

[0048] After particle addition and circulating mixing are completed, the first composite plating solution forms a low-particle-supply state, the second composite plating solution forms a medium-particle-supply state, and the third composite plating solution forms a high-particle-supply state. All three composite plating solutions have the same silver-based electrodeposition conditions, and the mass concentrations of silicon carbide and graphite particles added follow the same particle ratio gradient coefficient. The first composite plating solution is increased step by step to the third composite plating solution, which together constitutes the composite plating solution group used for the subsequent three continuous composite plating stages.

[0049] In step S4, the particle ratio differences of the composite plating solution group need to be transferred to the coating thickness direction in a predetermined order, and the state and ratio of each composite plating solution need to be maintained during the continuous composite plating process. The composite plating substrate is then subjected to continuous composite plating of the first, second, and third composite plating solutions in sequence, which is used to form composite layers with progressively increasing particle co-deposition levels while the silver matrix is ​​continuously growing.

[0050] Specifically, the first, second, and third composite plating solutions are respectively set in three composite plating stages arranged sequentially along the direction of the copper-based alloy sliding contact wire conductor. Each composite plating stage uses an independent circulation pipeline to maintain the dispersion state of the corresponding composite plating solution. The composite plating substrate continues to move and enters the three composite plating stages sequentially. The silver matrix grows continuously outward from the surface of the silver conductive support layer, and silicon carbide particles and graphite particles enter the first, second, and third composite layer segments respectively with silver electrodeposition. Between adjacent composite plating stages, the composite plating solution carried on the working surface and capable of flowing is removed, allowing the detached composite plating solution to return to the corresponding original composite plating solution tank. At the same time, the surface of the formed composite layer segment is kept moist and directly enters the next composite plating stage. The three composite layer segments are sequentially stacked to form a gradient multi-element composite working layer, obtaining a gradient composite plating conductor.

[0051] Before continuous composite plating begins, the circulation flow of three composite plating baths is initiated, allowing any particles that may have settled at the bottom of the baths to re-enter the main composite plating solution, and ensuring that silicon carbide and graphite particles continuously pass near the plating area. The circulation flow transports silicon carbide and graphite particles from the main composite plating solution to the working surface of the copper-based alloy sliding contact wire conductor. The intensity of the circulation flow is controlled by ensuring that there is no continuous particle deposit layer at the bottom of the composite plating bath, no long-term stagnant liquid areas in the plating area, and that the return liquid does not directly and strongly impact the cathode surface.

[0052] All three composite plating stages employed a non-cyanide sulfite silver electroplating system, with silver ion concentration controlled at 20-40 g / L, free sulfite concentration at 80-160 g / L, pH at 8.0-9.5, plating temperature at 25-40℃, and cathode current density at 0.5-2.0 A / dm³. 2 In the same continuous composite plating process, the silver ion concentration, free sulfite concentration, pH, and plating temperature in the three composite plating stages are all set with the same target values, so that the continuous metal matrix in the three composite layers is formed by the same silver electroplating system.

[0053] The composite plating substrate keeps the surface of the silver conductive support layer moist and enters the first composite plating stage. The silver conductive support layer serves as the direct cathode deposition surface. Silver complex ions gain electrons on the surface of the silver conductive support layer and are reduced, forming a silver matrix that grows continuously from the silver conductive support layer. Silicon carbide particles and graphite particles in the first composite plating solution flow into the vicinity of the cathode interface with the circulating flow, contacting the growing silver deposition surface. During the continued growth of the silver matrix, they are gradually surrounded and fixed, transforming from suspended particles in the composite plating solution into co-deposited particles embedded in the continuous silver phase.

[0054] The first composite plating bath employs the lowest mass ratio of silicon carbide and graphite particles among the three composite plating baths, creating a low-particle supply environment for the first composite plating stage. The cathode current density, effective plating length, and the passage speed of the copper-based alloy sliding contact wire conductor in the first composite plating stage are matched to ensure the first composite layer reaches the target thickness. The thickness of the first composite layer accounts for 25%-40% of the total thickness of the gradient multi-element composite working layer. The first composite layer employs the lowest particle co-deposition level among the three composite layers, maintaining a high proportion of continuous silver phase in the region near the silver conductive support layer.

[0055] After the first composite layer reaches the target thickness, a clean, oil-free gas is used to form a non-contact airflow that acts laterally on the working surface to remove the first composite plating solution carried on the surface of the first composite layer and capable of flowing or dripping. The separated first composite plating solution is returned to the first composite plating bath through a collection structure. The airflow is controlled to ensure that there is no continuous flowing liquid or dripping droplets on the working surface, while maintaining a continuous wet liquid film on the surface of the first composite layer. The first composite layer does not undergo intermediate water washing and drying and directly enters the second composite plating stage in a wet state.

[0056] Removing the flowable first composite plating solution reduces particle dilution caused by the introduction of low-particle-ratio plating solution into the second composite plating solution, and recirculating the original tank allows the first composite plating solution to continue to be used independently. Retaining a continuous wetting film limits the drying, salt residue formation, or surface oxidation that could affect further deposition on the surface of the first composite layer, allowing the second composite layer to continue growing from the continuous silver phase of the first composite layer.

[0057] The first composite layer, kept moist, enters the second composite plating stage. The source of silver ions, the complexation system, and the basic electrodeposition conditions in the second composite plating solution remain consistent with those in the first composite plating solution, but the added mass of silicon carbide and graphite particles in the second composite plating solution is higher than that in the first composite plating solution. Silver complex ions are reduced on the surface of the first composite layer, and the newly added silver atoms combine with the continuous silver on the surface of the first composite layer, allowing the silver matrix in the second composite layer to continue growing from the first composite layer. The silicon carbide particles and graphite particles in the second composite plating solution reach the silver deposition interface through circulation and are surrounded and fixed during the continuous growth of the silver matrix.

[0058] When the silver-based electrodeposition conditions and cycling states are basically the same, increasing the particle addition quality in the composite plating solution can increase the number of particles reaching the silver deposition interface and contacting the silver deposition surface per unit time, thereby increasing the chance of particles being surrounded and fixed by the silver matrix. Therefore, the co-deposition level of silicon carbide particles and graphite particles in the second composite layer is higher than that in the first composite layer. The thickness of the second composite layer formed in the second composite plating stage accounts for 30%-40% of the total thickness of the gradient multi-element composite working layer. The second composite layer undertakes the compositional change from low particle co-deposition level to high particle co-deposition level while maintaining the continuity of the silver matrix.

[0059] After the second composite layer reaches the target thickness, the same non-contact liquid control method is used to remove the second composite plating solution carried on the surface of the second composite layer and capable of flowing or dripping, allowing the separated second composite plating solution to return to the second composite plating bath. The surface of the second composite layer after liquid control maintains a continuous wet film, without intermediate rinsing or drying, and directly enters the third composite plating stage. The particle ratio plating solution in the original bath of the second composite plating solution is carried into the third composite plating solution, maintaining a high particle ratio relative to the second composite plating solution; this wet transfer allows the third composite layer to continue growing from the continuous silver phase of the second composite layer.

[0060] The source of silver ions, the complexation system, and the basic electrodeposition conditions in the third composite plating solution are consistent with those in the first and second composite plating solutions. The added mass of silicon carbide and graphite particles in the third composite plating solution is higher than that in the second composite plating solution. Silver complex ions are reduced on the surface of the second composite layer, and the silver matrix continues to grow outward from the continuous silver phase on the surface of the second composite layer. The mass of silicon carbide particles and graphite particles in the third composite plating solution reaches the deposition interface with the circulating flow and is surrounded and fixed by the growing silver matrix, resulting in a higher level of co-deposition of silicon carbide and graphite particles in the third composite layer compared to the second composite layer.

[0061] The thickness of the third composite layer accounts for 25%-40% of the total thickness of the gradient multi-element composite working layer. The sum of the actual thickness ratios of the first, second, and third composite layers is 100%, and the sum of the thicknesses of the three composite layers is 10-25 μm. The thickness of each composite layer is jointly controlled by the effective plating length of the corresponding composite plating stage, the cathode current density, and the passing speed of the copper-based alloy sliding contact wire conductor.

[0062] The first, second, and third composite layers use the same continuous silver metal matrix and form a continuous silver phase growth relationship through inter-stage controlled liquid wet transfer. The co-deposition level of silicon carbide particles and graphite particles increases progressively in the order of the first, second, and third composite layers, creating a stepped particle composition gradient on the outer side of the silver conductive support layer.

[0063] The low-particle co-deposition level in the first composite layer maintains a high proportion of continuous silver phase on the inner side of the gradient multi-component composite working layer, forming a current-carrying region extending along the length of the copper-based alloy sliding contact wire conductor together with the silver conductive support layer. The second composite layer improves the quality of silicon carbide particles and the content of graphite particles, creating a compositional transition between the continuous silver phase and the outer wear-resistant and friction-reducing region. The third composite layer is located in the outer working region that directly participates in sliding contact. Silicon carbide particles enhance the silver matrix's resistance to mechanical ploughing and localized plastic deformation, while graphite particles are gradually exposed during sliding contact and wear, forming a lubricating contact region.

[0064] The composite electrodeposition process ends after the third composite layer reaches the target thickness. The copper-based alloy substrate, nickel transition layer, silver conductive support layer, and gradient multi-component composite working layer are sequentially connected to form a gradient composite plated conductor.

[0065] In step S5, after the gradient composite plated conductor leaves the third composite plating solution, the surface of the gradient multi-component composite working layer carries soluble plating solution components such as silver salts and sulfites, and may also have free silicon carbide particles and graphite particles that are not fixed by the silver matrix attached. It is necessary to remove surface residues and wash away moisture while maintaining the surface morphology of the third composite layer segment and the particle composition gradient of the three composite layers to form a stable working surface suitable for sliding contact.

[0066] To complete the post-plating treatment, the gradient multi-component composite working layer undergoes a series of processes: pre-washing, rinsing, surface dehydration, and hot air drying. Pre-washing displaces most of the third composite plating solution carried on the working surface and removes free particles not fixed by the silver matrix. Rinsing further removes residual soluble plating solution components and free particles. Surface dehydration removes any flowing or accumulating cleaning water, and hot air drying removes residual water film and localized water accumulation. During the post-plating treatment, no mechanical leveling or material removal is performed on the gradient multi-component composite working layer, ensuring that the silicon carbide particles embedded in the silver matrix and the graphite particles remain within their respective composite layer segments.

[0067] In practice, a continuous flow of cleaning water is used for the initial rinsing of the gradient multi-component composite working layer, with the cleaning water temperature controlled between 15-35℃. After the cleaning water comes into contact with the third composite plating solution carried on the working surface, it dilutes and displaces the third composite plating solution, allowing silver salts, sulfites, and other water-soluble components to enter the cleaning water. The flow of the cleaning water simultaneously removes silicon carbide and graphite particles that remain on the surface of the third composite layer but are not surrounded and fixed by the silver matrix. The intensity of the water flow is controlled to disrupt the liquid film carried on the working surface and remove free particles, without causing scratches, peeling, or localized material detachment from the surface of the third composite layer.

[0068] After the initial water rinse, the working surface is continuously cleaned with water to further replace any remaining pre-cleaning solution in the micro-recesses and edges of the surface. The water rinse is completed when there are no visible composite plating solution residues, particle buildup, or discontinuous water films on the working surface, and the water flowing over the surface no longer carries visible solid particles. The water rinse process does not involve mechanical brushing, grinding, or polishing, ensuring that the silicon carbide and graphite particles, which have entered the third composite layer and are surrounded and fixed by the silver matrix, remain within the continuous silver phase.

[0069] After water washing, a clean, oil-free gas is used to form a non-contact dewatering airflow, blowing away any cleaning water that flows along the working surface or accumulates at the edges from the gradient multi-component composite working layer. Dewatering is completed when there is no continuous flowing water, dripping water, or water accumulation at the edges of the working surface. Hot air at 50-80℃ is used to continuously dry the dewatered gradient composite plated conductor, evaporating any moisture remaining in the micro-recesses, interparticle gaps, and edges, and expelling it with the airflow. The hot air temperature is controlled at 50-80℃ to increase the moisture evaporation rate and prevent excessively high temperatures from causing discoloration of the silver matrix surface, localized oxidation, or thermal deformation of the copper-based alloy sliding contact wire conductor.

[0070] After drying, the working surface of the copper-based alloy sliding contact wire conductor consists of, from the inside out, a nickel transition layer with a thickness of 0.5-2.0 μm, a silver conductive support layer with a thickness of 3-8 μm, and a gradient multi-component composite working layer with a total thickness of 10-25 μm. The gradient multi-component composite working layer includes a first composite layer segment, a second composite layer segment, and a third composite layer segment formed continuously. The co-deposition level of silicon carbide particles and graphite particles increases progressively from the silver conductive support layer side towards the sliding working surface, resulting in a copper-based alloy sliding contact wire conductor with a surface multi-component composite coating.

[0071] Example 1:

[0072] This embodiment provides a method for multi-element composite plating of the surface of a copper-based alloy sliding contact wire conductor, the specific process of which is as follows.

[0073] S1: The working surface of the copper-chromium-zirconium alloy sliding contact line conductor is continuously degreased using an alkaline degreasing solution at a temperature of 50°C. The treatment time of the working surface in the degreasing area is 3 minutes. After degreasing, the surface is continuously rinsed with running water until there is no visible oil film, foam, or degreasing solution residue on the working surface, and the water can be continuously spread on the working surface.

[0074] The working surface was continuously micro-etched using a sulfuric acid-hydrogen peroxide micro-etching solution with a sulfuric acid concentration of 80 g / L and a hydrogen peroxide concentration of 25 g / L. The micro-etching temperature was 30℃, the micro-etching time was 60 s, and the micro-etching depth was 0.8 μm. After micro-etching, residual micro-etching solution, copper ions, and dissolution products were removed using running water, and a continuous water film was maintained on the working surface.

[0075] The washed working surface was activated using a 50 g / L sulfuric acid aqueous solution at 25°C for 30 seconds. After activation, the sulfuric acid activating solution on the working surface was replaced with running water to keep the surface moist and form an activated copper-based surface.

[0076] S2: To maintain the cathode conductivity of the copper-chromium-zirconium alloy sliding contact wire conductor, the active copper-based surface is immersed in a nickel plating bath for nickel electrodeposition. The nickel ion concentration in the nickel plating bath is 75 g / L, the pH is 4.2, the bath temperature is 50℃, and the cathode current density is 2.0 A / dm³. 2 Nickel ions are reduced on the active copper substrate surface to form a continuous nickel layer. Nickel electrodeposition continues until the nickel layer thickness reaches 1.0 μm, forming a continuous nickel transition layer covering the active copper substrate surface. Flowing water is used to displace the nickel plating solution carried on the surface of the nickel transition layer, keeping the nickel transition layer moist.

[0077] A nickel transition layer was used as the deposition surface, and silver electrodeposition was performed using a non-cyanide sulfite silver electroplating system. The silver ion concentration in the silver plating bath was 30 g / L, the free sulfite concentration was 120 g / L, the pH was 8.5, the bath temperature was 35℃, and the cathode current density was 1.0 A / dm³. 2 During silver electrodeposition, no silicon carbide or graphite particles are added to the silver plating bath. Silver electrodeposition continues until the silver layer thickness reaches 5.0 μm, forming a silver conductive support layer that continuously covers the nickel transition layer. The silver plating bath that can continuously flow on the surface of the silver conductive support layer is removed, while keeping the silver conductive support layer wet, to obtain a composite plating substrate.

[0078] S3: Prepare three composite plating solutions, each with a final volume of 30L: a first composite plating solution, a second composite plating solution, and a third composite plating solution. All three composite plating solutions use a non-cyanide sulfite-based silver plating solution with a silver ion concentration of 30g / L, a free sulfite concentration of 120g / L, and a pH of 8.5. Each of the three composite plating solution tanks uses an independent storage space and circulation pipeline.

[0079] Silicon carbide particles were added to an aqueous dispersion medium, along with a nonionic dispersant at a mass of 1.0% of the silicon carbide particles. Graphite particles were added to another aqueous dispersion medium, along with a nonionic dispersant at a mass of 1.0% of the graphite particles. Both types of particles were mechanically stirred and ultrasonically dispersed for 25 minutes each, yielding a silicon carbide particle dispersion with a mass concentration of 100 g / L and a graphite particle dispersion with a mass concentration of 75 g / L.

[0080] The first composite plating solution uses 3.0 g / L silicon carbide particles and 1.0 g / L graphite particles. Based on a final volume of 30 L for the first composite plating solution, 0.90 L of silicon carbide particle dispersion containing 90 g of silicon carbide particles and 0.40 L of graphite particle dispersion containing 30 g of graphite particles are added.

[0081] The second composite plating solution uses 5.7 g / L silicon carbide particles and 1.9 g / L graphite particles. Based on a final volume of 30 L for the second composite plating solution, 1.71 L of silicon carbide particle dispersion containing 171 g of silicon carbide particles and 0.76 L of graphite particle dispersion containing 57 g of graphite particles were added.

[0082] The third composite plating solution uses 10.8 g / L silicon carbide particles and 3.6 g / L graphite particles. Based on a final volume of 30 L for the third composite plating solution, 3.24 L of silicon carbide particle dispersion containing 324 g of silicon carbide particles and 1.44 L of graphite particle dispersion containing 108 g of graphite particles were added.

[0083] When preparing each composite plating solution, the corresponding silicon carbide particle dispersion was continuously added to the mixing zone of the circulating plating solution. The mixture was circulated and mixed until the silicon carbide particles were dispersed throughout the main plating solution. Then, the corresponding graphite particle dispersion was added to the same mixing zone. After both types of particle dispersions were added, silver complexing solution, sulfite, and water were added to ensure that the final volume of each composite plating solution was 30L. The silver ion concentration was adjusted to 30g / L, the free sulfite concentration to 120g / L, and the pH to 8.5.

[0084] The first composite plating solution, the second composite plating solution, and the third composite plating solution are circulated and mixed in their respective composite plating solution tanks and circulation pipelines until there is no continuous particle deposition layer at the bottom of the tank, no visible large-sized agglomerates in the main composite plating solution, and no large-scale floating particles on the liquid surface, thus obtaining a composite plating solution group.

[0085] S4: The first, second, and third composite plating solutions are respectively set in the first, second, and third composite plating stages arranged sequentially along the direction of the copper-chromium-zirconium alloy sliding contact wire conductor. Each of the three composite plating stages uses an independent circulation pipeline to maintain the circulation and dispersion of the corresponding composite plating solution. The temperature of all composite plating solutions is 35℃, and the cathode current density is 1.0 A / dm³. 2 The continuous throughput speed of the copper-chromium-zirconium alloy sliding contact line conductor is 0.20 m / min.

[0086] The composite plating substrate is kept moist on the surface of the silver conductive support layer and enters the first composite plating bath. Silver complex ions are reduced on the surface of the silver conductive support layer. Silicon carbide particles and graphite particles in the first composite plating bath enter the silver deposition interface with the circulating plating bath and grow into the first composite layer segment along with the silver matrix. The first composite plating stage continues until the thickness of the first composite layer segment reaches 6.0 μm.

[0087] After the first composite layer segment leaves the first composite plating solution, a clean, oil-free gas is used to form a non-contact airflow that acts laterally on the working surface to remove any flowing or dripping first composite plating solution from the surface of the first composite layer segment. The separated first composite plating solution returns to the first composite plating solution tank. After liquid control, the surface of the first composite layer segment is free of continuously flowing liquid and dripping droplets, and maintains a continuous wet film before directly entering the second composite plating solution.

[0088] The silver matrix continues to grow from the continuous silver phase on the surface of the first composite layer, while silicon carbide and graphite particles in the second composite plating solution grow into the second composite layer along with the silver matrix. The second composite plating stage continues until the thickness of the second composite layer reaches 6.0 μm.

[0089] After the second composite layer segment leaves the second composite plating bath, the same non-contact airflow removes any remaining flowable and dripping second composite plating bath from its surface. The separated second composite plating bath returns to the second composite plating bath tank. The surface of the second composite layer segment, after liquid control, maintains a continuous wet film and directly enters the third composite plating bath.

[0090] The silver matrix continues to grow from the continuous silver phase on the surface of the second composite layer. Silicon carbide and graphite particles in the third composite plating solution grow into the third composite layer along with the silver matrix. The third composite plating stage continues until the thickness of the third composite layer reaches 6.0 μm. The first, second, and third composite layers together form a gradient multi-element composite working layer with a total thickness of 18.0 μm, obtaining a gradient composite plated conductor.

[0091] S5: A pre-wash of the gradient multi-component composite working layer is performed using continuously flowing cleaning water at 25°C to replace the third composite plating solution carried on the working surface and remove free particles not fixed by the silver matrix. After the pre-wash, a second continuous wash is performed on the working surface using water at 25°C until there are no visible composite plating solution residues or particle accumulations on the working surface, and the water flowing over the working surface no longer carries visible solid particles.

[0092] Clean, oil-free gas is used to form a non-contact dehydration airflow to remove any flowing or accumulating cleaning water from the working surface. The dehydrated gradient composite-plated conductor is then continuously dried with 60°C hot air until no visible water film, droplets, or damp areas remain on the working surface. After drying, a copper-based alloy sliding contact wire conductor with a multi-element composite plating is obtained.

[0093] Example 2:

[0094] The difference between Example 2 and Example 1 is that in S3, the first composite plating solution uses 3.0 g / L silicon carbide particles and 1.0 g / L graphite particles, and 0.90 L silicon carbide particle dispersion and 0.40 L graphite particle dispersion are added.

[0095] The second composite plating solution uses 6.3 g / L silicon carbide particles and 2.1 g / L graphite particles. 1.89 L of silicon carbide particle dispersion containing 189 g of silicon carbide particles and 0.84 L of graphite particle dispersion containing 63 g of graphite particles are added to a final volume of 30 L.

[0096] The third composite plating solution uses 13.2 g / L silicon carbide particles and 4.4 g / L graphite particles. A 3.96 L silicon carbide particle dispersion containing 396 g silicon carbide particles and a 1.76 L graphite particle dispersion containing 132 g graphite particles are added to a final volume of 30 L.

[0097] The silver ion concentration, free sulfite concentration, and pH in the three composite plating solutions were adjusted to 30 g / L, 120 g / L, and 8.5, respectively. Except for the foregoing, the remaining steps and implementation conditions of this embodiment are consistent with those of Example 1, resulting in a copper-based alloy sliding contact wire conductor with a multi-element composite plating.

[0098] Example 3:

[0099] The difference between Example 3 and Example 1 is that in S3, the first composite plating solution uses 3.0 g / L silicon carbide particles and 1.0 g / L graphite particles, and 0.90 L silicon carbide particle dispersion and 0.40 L graphite particle dispersion are added.

[0100] The second composite plating solution uses 6.9 g / L silicon carbide particles and 2.3 g / L graphite particles. 2.07 L of silicon carbide particle dispersion containing 207 g silicon carbide particles and 0.92 L of graphite particle dispersion containing 69 g graphite particles are added to a final volume of 30 L.

[0101] The third composite plating solution uses 15.9 g / L silicon carbide particles and 5.3 g / L graphite particles. 4.77 L of silicon carbide particle dispersion containing 477 g silicon carbide particles and 2.12 L of graphite particle dispersion containing 159 g graphite particles are added to a final volume of 30 L.

[0102] The silver ion concentration, free sulfite concentration, and pH in the three composite plating solutions were adjusted to 30 g / L, 120 g / L, and 8.5, respectively. Except for the foregoing, the remaining steps and implementation conditions of this embodiment are consistent with those of Example 1, resulting in a copper-based alloy sliding contact wire conductor with a multi-element composite plating.

[0103] Example 4:

[0104] The difference between Example 4 and Example 1 is that in S3, the first composite plating solution uses 3.0 g / L silicon carbide particles and 1.0 g / L graphite particles, and 0.90 L silicon carbide particle dispersion and 0.40 L graphite particle dispersion are added.

[0105] The second composite plating solution uses 7.2 g / L silicon carbide particles and 2.4 g / L graphite particles. 2.16 L of silicon carbide particle dispersion containing 216 g silicon carbide particles and 0.96 L of graphite particle dispersion containing 72 g graphite particles are added to a final volume of 30 L.

[0106] The third composite plating solution uses 17.3 g / L silicon carbide particles and 5.8 g / L graphite particles. 5.19 L of silicon carbide particle dispersion containing 519 g silicon carbide particles and 2.32 L of graphite particle dispersion containing 174 g graphite particles are added to a final volume of 30 L.

[0107] The silver ion concentration, free sulfite concentration, and pH in the three composite plating solutions were adjusted to 30 g / L, 120 g / L, and 8.5, respectively. Except for the foregoing, the remaining steps and implementation conditions of this embodiment are consistent with those of Example 1, resulting in a copper-based alloy sliding contact wire conductor with a multi-element composite plating.

[0108] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that in S3, the first composite plating solution uses 3.0 g / L silicon carbide particles and 1.0 g / L graphite particles, and 0.90 L silicon carbide particle dispersion and 0.40 L graphite particle dispersion are added.

[0109] The second composite plating solution uses 4.8 g / L silicon carbide particles and 1.6 g / L graphite particles. A 1.44 L silicon carbide particle dispersion containing 144 g silicon carbide particles and a 0.64 L graphite particle dispersion containing 48 g graphite particles are added to a final volume of 30 L.

[0110] The third composite plating solution uses 7.7 g / L silicon carbide particles and 2.6 g / L graphite particles. 2.31 L of silicon carbide particle dispersion containing 231 g of silicon carbide particles and 1.04 L of graphite particle dispersion containing 78 g of graphite particles are added to a final volume of 30 L.

[0111] The silver ion concentration, free sulfite concentration, and pH in the three composite plating solutions were adjusted to 30 g / L, 120 g / L, and 8.5, respectively. Except for the foregoing, the remaining steps and implementation conditions of this comparative example were consistent with those of Example 1, resulting in a copper-based alloy sliding contact wire conductor with a multi-element composite plating.

[0112] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that in S3, the first composite plating solution uses 3.0 g / L silicon carbide particles and 1.0 g / L graphite particles, and 0.90 L silicon carbide particle dispersion and 0.40 L graphite particle dispersion are added.

[0113] The second composite plating solution uses 7.8 g / L silicon carbide particles and 2.6 g / L graphite particles. 2.34 L of silicon carbide particle dispersion containing 234 g silicon carbide particles and 1.04 L of graphite particle dispersion containing 78 g graphite particles are added to a final volume of 30 L.

[0114] The third composite plating solution uses 20.3 g / L silicon carbide particles and 6.8 g / L graphite particles. A 6.09 L silicon carbide particle dispersion containing 609 g silicon carbide particles and a 2.72 L graphite particle dispersion containing 204 g graphite particles are added to a final volume of 30 L.

[0115] The silver ion concentration, free sulfite concentration, and pH in the three composite plating solutions were adjusted to 30 g / L, 120 g / L, and 8.5, respectively. Except for the foregoing, the remaining steps and implementation conditions of this comparative example were the same as in Example 1, resulting in a copper-based alloy sliding contact wire conductor with a multi-element composite plating on the surface.

[0116] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that in S3, the first composite plating solution, the second composite plating solution, and the third composite plating solution all use 8.0 g / L silicon carbide particles and 2.5 g / L graphite particles.

[0117] Based on a final volume of 30L for each composite plating solution, 2.40L of silicon carbide particle dispersion containing 240g of silicon carbide particles and 1.00L of graphite particle dispersion containing 75g of graphite particles were added to the first, second, and third composite plating solutions, respectively. The silver ion concentration, free sulfite concentration, and pH of the three composite plating solutions were adjusted to 30g / L, 120g / L, and 8.5, respectively, and then circulated and mixed separately.

[0118] In step S4, the composite plating substrate is sequentially introduced into the first composite plating solution, the second composite plating solution, and the third composite plating solution, forming a composite layer segment with a thickness of 6.0 μm in each composite plating stage. The adjacent composite plating stages are separated by the same non-contact controlled wet transfer treatment as in Example 1, and the three composite layer segments together form a composite working layer with a total thickness of 18.0 μm.

[0119] Except for the foregoing, the remaining steps and implementation conditions of this comparative example are the same as those in Example 1, resulting in a surface-coated copper-based alloy sliding contact wire conductor.

[0120] Comparative Example 4: The difference between Comparative Example 4 and Example 3 is that, in S4, after the first composite layer reaches 6.0 μm, the copper-chromium-zirconium alloy sliding contact wire conductor carries the first composite plating solution directly into the second composite plating solution. The flowable first composite plating solution on the surface of the first composite layer enters the second composite plating solution tank along with the copper-chromium-zirconium alloy sliding contact wire conductor, and the first composite layer undergoes the second stage of composite plating while in a liquid state.

[0121] After the second composite layer reaches 6.0 μm, the copper-chromium-zirconium alloy sliding contact wire conductor carries the second composite plating solution directly into the third composite plating solution. The flowable second composite plating solution on the surface of the second composite layer enters the third composite plating solution tank along with the copper-chromium-zirconium alloy sliding contact wire conductor, and the second composite layer undergoes the third stage of composite plating while in a liquid state.

[0122] After the third composite layer reaches 6.0 μm, the continuous composite plating ends, and the three composite layers together form a composite working layer with a total thickness of 18.0 μm. Except for the aforementioned inter-stage liquid direct transfer method, the remaining steps and implementation conditions of this comparative example are the same as those in Example 3, and a surface multi-component composite plated copper-based alloy sliding contact wire conductor is obtained.

[0123] Experimental Example 1: The experimental subjects in this example include the surface multi-component composite plated copper-based alloy sliding contact wire conductors formed in Examples 1 to 4, and the surface multi-component composite plated copper-based alloy sliding contact wire conductors formed in Comparative Examples 1 to 4.

[0124] In this experimental example, the following tests were performed respectively.

[0125] 1. Particle composition gradient difference test: The particle composition gradient difference is used to evaluate the actual difference in particle composition between the first composite layer and the third composite layer.

[0126] The morphology of the first, second, and third composite layers in the cross-sectional sample was observed using scanning electron microscopy (SEM), and the silicon element distribution was obtained using energy dispersive spectroscopy (EDS). Silicon carbide particles were identified based on the location of silicon element distribution. Micro-Raman spectroscopy was used to perform surface scanning on the same cross-sectional region, and graphite particles were identified based on the D and G peaks corresponding to graphite. The EDS and Raman surface scanning images were registered with the cross-sectional microscopic images, respectively. Five mutually separate cross-sectional fields of view were selected for each composite layer, and the area fractions of silicon carbide and graphite particles in the corresponding fields of view were calculated using image analysis software. Based on the stereochemical relationship of random cross-sectional sampling, the particle area fraction was used as an estimate of the corresponding particle volume fraction, and the average value of the five fields of view was calculated.

[0127] The particle composition gradient difference was calculated using the detection results from a location 15m from the starting end of the conductor. : In the formula, and These represent the volume fractions of silicon carbide particles and graphite particles in the third composite layer, respectively. and These represent the volume fractions of silicon carbide particles and graphite particles in the first composite layer, respectively. Particle composition gradient difference. The unit is volume percentage. The increase indicates that the particle composition increment of the third composite layer is higher than that of the first composite layer.

[0128] 2. Length direction particle composition variation coefficient test: The length direction particle composition variation coefficient is used to evaluate the stability of the particle composition of the third composite layer along the conductor length direction during continuous composite plating.

[0129] Using the same detection method as the particle composition gradient difference test, the volume fractions of silicon carbide particles and graphite particles in the third composite layer at positions 5m, 15m, and 25m from the conductor's starting end were obtained. The sum of the volume fractions of the two types of particles at the same location was taken as the total particle volume fraction of the third composite layer.

[0130] The coefficient of variation (CV) of particle composition along the length direction is calculated as the ratio of the standard deviation to the mean of the total particle volume fraction at the three sampling locations. In the formula, This represents the standard deviation of the total particle volume fraction at the three sampling locations. This represents the average total particle volume fraction at three sampling locations. Three parallel, spaced scratches were created at each sampling location, and the average value was calculated. A decrease in CV indicates a reduction in the change in particle composition of the third composite layer as the continuous processing length increases.

[0131] 3. Interlayer bonding critical load test: The interlayer bonding critical load is used to evaluate the continuous bonding state between the silver conductive support layer and the three composite segments.

[0132] The test was conducted using an incremental load scratch tester with a diamond indenter having a tip radius of 200 μm. The indenter created a 5 mm long linear scratch on the surface of the gradient multi-component composite working layer at a scratching speed of 5 mm / min, and the applied force increased linearly from 1 N to 20 N along the scratch direction.

[0133] During the scratching process, scratch friction and acoustic emission signals were recorded simultaneously. After the scratching was completed, the scratch edges and interior were observed using an optical microscope. The loading force corresponding to the first occurrence of continuous spalling or penetrating interlayer delamination was determined as the critical load for interlayer bonding. The unit is N. Three parallel and spaced scratches are formed at each sampling location, and the average value is calculated. The increase indicates an improved ability of the silver conductive support layer and adjacent composite layers to withstand shear loads without discontinuous separation.

[0134] 4. Contact resistance test: Contact resistance is used to evaluate the current-carrying state formed by the silver conductive support layer and the gradient multi-component composite working layer.

[0135] A four-wire microresistance testing device was used, with a copper-graphite contact block as the mating component, ensuring contact between the copper-graphite contact block and the surface of the third composite layer. During testing, a 20N normal load was applied, and a 10A DC test current was passed. The voltage drop was recorded after maintaining the contact state for 10 seconds. And calculate the contact resistance according to the following formula. : In the formula, The test current is 10A. This represents the voltage drop between the copper-graphite contact block and the test sample. Contact resistance. The unit is mΩ. Five separate test points are selected at each sampling location, and the average value of the five test points is taken. A decrease in contact resistance indicates that the continuous silver phase current-carrying path in the gradient multi-element composite working layer is more complete.

[0136] 5. Friction Coefficient Test: The sliding friction state of the gradient multi-component composite working layer was tested using a ball-disc friction and wear testing machine. The mating component consisted of alumina ceramic balls, with a normal load of 5 N, a sliding speed of 0.1 m / s, and a sliding distance of 1000 m. Friction force was continuously recorded during the test.

[0137] The average friction coefficient is defined as the ratio of the average friction force to the normal load during the sliding distance range of 100-1000m. Three separate friction trajectories are set at each sampling location, and the average value is calculated. A decrease in the average friction coefficient indicates a reduction in the sliding resistance of the gradient multi-component composite working layer surface.

[0138] 6. Wear Measurement Test: After the friction coefficient test is completed, a three-dimensional optical profilometer is used to scan the complete wear track area. The cross-sectional profile of the wear track is continuously acquired along the length of the wear track. A reference surface is established based on the unworn surface. The material loss volume of the wear track below the reference surface is calculated, and the material loss volume of the complete wear track is taken as the wear measurement.

[0139] The unit of wear measurement is mm. 3 Each sampling location corresponds to three friction trajectories, and the average wear amount of the three friction trajectories is calculated. A decrease in wear amount indicates an improved ability of the gradient multi-component composite working layer to resist mechanical plowing, localized plastic deformation, and material separation.

[0140] The results are shown in the table below: Table 1

[0141] Examples 1 to 4 used the same particle ratio in the first composite plating solution, and the particle addition mass in the second and third composite plating solutions was changed by adjusting the particle ratio gradient coefficient. As the particle ratio gradient coefficient increased from 1.9 to 2.3, the number of silicon carbide and graphite particles per unit volume of the composite plating solution gradually increased in the second and third composite plating solutions. When the silver ion concentration, cathode current density, plating temperature, and cycling conditions remained consistent, the number of particles reaching the silver deposition interface in the second and third composite plating stages increased accordingly, and the number of particles surrounded and fixed by the grown silver matrix also increased, causing the particle composition gradient difference to gradually increase.

[0142] In Example 1, the particle size distribution gradient coefficient was 1.9. The added mass of silicon carbide particles in the first, second, and third composite plating solutions were 3.0 g / L, 5.7 g / L, and 10.8 g / L, respectively, while the added mass of graphite particles were 1.0 g / L, 1.9 g / L, and 3.6 g / L, respectively. A difference in particle composition was established between the three composite layers, with a particle composition gradient difference of 4.8 vol.%. The supply levels of silicon carbide and graphite particles in the third composite layer were at the lower end of the Example group, resulting in a relatively small number of hard particle bearing areas and graphite lubrication contact areas formed on the working surface. Therefore, the average friction coefficient was 0.181, and the wear was 3.4 × 10⁻⁶. -3 mm 3 The lower content of outer particles results in a higher proportion of continuous silver phase, maintaining a contact resistance of 0.48 mΩ.

[0143] In Example 2, the particle size distribution gradient coefficient was increased to 2.1, improving the supply levels of both types of particles in the second and third composite plating solutions. The particle composition gradient difference increased to 6.5 vol.%, increasing the number of hard support positions formed by silicon carbide particles in the third composite layer and correspondingly increasing the lubricating contact area formed by graphite particles during sliding. The average coefficient of friction decreased to 0.158, and the wear amount decreased to 2.7 × 10⁻⁶. -3 mm 3 The three composite segments are still continuously formed from the same silver matrix. Inter-stage controlled wet transfer limits cross-mixing of the composite plating solution and keeps the surface of the composite segments wet, increasing the critical load for interlayer bonding to 14.1 N. The increased particle content occupies part of the continuous silver phase space, causing the contact resistance to increase to 0.52 mΩ compared to Example 1.

[0144] In Example 3, the particle size distribution gradient coefficient was 2.3. The added mass of silicon carbide particles in the first, second, and third composite plating solutions were 3.0 g / L, 6.9 g / L, and 15.9 g / L, respectively, while the added mass of graphite particles were 1.0 g / L, 2.3 g / L, and 5.3 g / L, respectively. The particle composition gradient difference reached 8.2 vol.%, and the coefficient of variation in the length direction was 4.1%. The three composite plating solutions were maintained in an independent circulating dispersion state. During the inter-stage process, flowable and dripping composite plating solutions were removed and returned to the original composite plating solution tank, ensuring that the particle size distribution difference was maintained along the continuous processing length. The first composite layer maintained a high proportion of continuous silver phase, the second composite layer formed a particle composition transition, and the third composite layer formed a relatively high level of co-deposition of wear-resistant and lubricating particles.

[0145] In Example 3, the silver matrix grew continuously between the three composite plating stages. During the wet transfer, the surface of the composite layer did not undergo washing or drying, and the critical interlayer bonding load reached 15.4 N. In the third composite layer, silicon carbide particles limited the silver matrix from localized plastic deformation and mechanical ploughing under frictional loads. Graphite particles were gradually exposed with surface wear, reducing sliding shear resistance and lowering the average friction coefficient to 0.143, resulting in a wear amount of 2.2 × 10⁻⁶. -3 mm 3 The inner silver conductive support layer and the first composite layer segment maintain a continuous silver phase, with a contact resistance of 0.56 mΩ.

[0146] In Example 4, the particle ratio gradient coefficient increased to 2.4, and the added mass of silicon carbide particles and graphite particles in the third composite plating solution increased to 17.3 g / L and 5.8 g / L, respectively, increasing the particle composition gradient difference to 9.1 vol.%. As the total particle content in the third composite plating solution approached the higher end of the implementation range, the opportunities for contact and agglomeration between particles increased, and the fluctuation of particle distribution at different locations in the circulating plating solution increased accordingly, causing the coefficient of variation of the composition in the length direction to increase from 4.1% in Example 3 to 6.2%.

[0147] As the number of particles in the third composite layer continues to increase, the continuous growth space required for the silver matrix to surround adjacent particles decreases, and localized particle-rich regions affect silver phase bonding and load transfer. Contact resistance increases to 0.67 mΩ, and the critical interlayer bonding load decreases to 14.2 N. The surface effects of graphite and silicon carbide particles remain, but localized agglomeration and reduced silver matrix continuity increase material detachment from the friction trajectory, causing the average friction coefficient and wear rate to rise back to 0.151 and 2.5 × 10⁻⁶, respectively. -3 mm 3 In Example 4, the particle composition gradient continued to increase, while the contact resistance, interlayer bonding, and tribological indicators showed a turning point, corresponding to the combined effect of enhanced particle gradient and local particle enrichment.

[0148] The particle size distribution gradient coefficient in Comparative Example 1 was 1.6. The silicon carbide particles in the second composite plating solution and the two types of particles in the third composite plating solution were both lower than the corresponding addition masses used in the Example group. The particle supply differences between the first, second, and third composite layers were small, with a particle composition gradient difference of only 2.4 vol.%. The lower particle supply level allowed the third composite layer to maintain a higher proportion of continuous silver phase, resulting in a contact resistance of 0.43 mΩ and a length-direction composition variation coefficient of 4.0%. The number of silicon carbide particles in the third composite layer was insufficient to form a sufficiently dispersed bearing area, and the number of graphite particles was insufficient to form a continuously distributed lubricating contact area in the friction trajectory, resulting in an average friction coefficient of 0.218 and a wear amount of 4.7 × 10⁻⁶. -3 mm 3 The lower side is mainly characterized by the degree of gradient formation and insufficient supply of wear-resistant and friction-reducing particles on the outer side.

[0149] In Comparative Example 2, the particle size distribution gradient coefficient was 2.6, and the added mass of silicon carbide particles and graphite particles in the third composite plating bath were 20.3 g / L and 6.8 g / L, respectively. The particle composition gradient difference increased to 9.7 vol.%, but the high particle concentration increased the probability of particle collision and agglomeration, and some particles formed local enrichment during circulation, transport, and co-deposition. During continuous treatment, the particle settling, redispersion, and local agglomeration states changed with the treatment length, causing the coefficient of variation of composition along the length direction to increase to 11.8%.

[0150] After excessive particles enter the third composite layer, the continuous silver phase is separated by more particle interfaces, and particles in locally enriched regions cannot be completely and stably surrounded by the silver matrix. The contact resistance increases to 0.91 mΩ, and the critical load for interlayer bonding decreases to 10.1 N. While the increased total amount of silicon carbide and graphite particles still provides wear resistance and lubrication, the agglomerated particles form localized protrusions and detachment sites under sliding loads. These detached sites further participate in abrasive wear, resulting in an average friction coefficient and wear rate of 0.183 and 3.6 × 10⁻⁶, respectively. -3 mm 3 The higher concentration is mainly manifested as an imbalance in particle dispersion, a reduction in the silver continuous phase, and a decrease in the local particle fixation state, which leads to different results compared to the insufficient particle supply in Comparative Example 1.

[0151] In Comparative Example 3, the first, second, and third composite plating solutions all used 8.0 g / L silicon carbide particles and 2.5 g / L graphite particles. The three composite plating stages provided essentially the same particle supply level to the silver deposition interface, resulting in similar particle compositions in the first and third composite layers, with a particle composition gradient difference of 0.3 vol.%. The particle content in the three composite layers did not exhibit a progressive relationship from low to high along the coating thickness direction.

[0152] The uniform particle ratio results in a higher particle count in the first composite layer near the silver conductive support layer compared to the first composite layer in Example Group 1. This leads to greater separation of the inner connection state of the continuous silver phase by particle interfaces, resulting in a contact resistance of 0.63 mΩ. The particle supply level in the third composite layer is lower than in Examples 3 and 4, with insufficient wear-resistant and lubricating particles on the outer side, resulting in an average friction coefficient of 0.190 and a wear amount of 4.0 × 10⁻⁶. -3 mm 3 The same particle ratio was used to change both the inner silver phase ratio and the outer particle supply state, resulting in the failure to form a structure with current-carrying regions, transition regions, and wear-resistant and friction-reducing regions respectively arranged along the thickness direction.

[0153] Comparative Example 4 used the same initial ratio of three composite plating solutions as Example 3, but the first composite layer section carried the flowable first composite plating solution directly into the second composite plating solution, and the second composite layer section carried the flowable second composite plating solution directly into the third composite plating solution. The low-particle-ratio composite plating solution entered the subsequent composite plating solutions along with the continuously moving conductor, causing instantaneous dilution of the second and third composite plating solutions near the conductor inlet. As the continuous processing length increased, the preceding composite plating solution accumulated in the subsequent composite plating solutions, causing the actual particle supply state of the subsequent composite plating solutions to change along the conductor length direction.

[0154] Inter-stage liquid transfer reduced the particle composition gradient difference in Comparative Example 4 from 8.2 vol.% in Example 3 to 6.9 vol.%, and increased the coefficient of variation in length-direction composition from 4.1% to 13.5%. The flowing liquid film entering the next composite plating stage formed a short-term mixed plating region on the cathode surface, causing fluctuations in particle supply and silver deposition at the interface between adjacent composite layers. Localized uneven particle distribution and changes in particle coating state reduced the critical load for interlayer bonding to 9.6 N and increased the contact resistance to 0.72 mΩ. The actual particle supply in the third composite layer was lower than the supply state formed by the corresponding initial ratio, and the average friction coefficient and wear amount increased to 0.174 and 3.2 × 10⁻⁶, respectively. -3 mm 3 .

Claims

1. A method for surface multi-element composite plating of a copper-based alloy sliding contact wire conductor, characterized in that, Includes the following steps: S1: Pre-treatment of the working surface of the copper-based alloy sliding contact line conductor before plating is performed to form an active copper-based surface; S2: A metal transition layer and a conductive support layer are sequentially formed on the surface of an active copper substrate to obtain a composite plating substrate; S3: Configure the first composite plating solution, the second composite plating solution and the third composite plating solution, so that the mass ratio of silicon carbide particles and graphite particles added in each composite plating solution increases step by step from the first composite plating solution to the third composite plating solution, to obtain a composite plating solution group. S4: Using a composite plating solution group, the composite plating substrate is continuously composite plating in the order of the first composite plating solution to the third composite plating solution, and the circulation and dispersion state of each composite plating solution is maintained to form a gradient multi-element composite working layer and obtain a gradient composite plating conductor. S5: Perform post-plating treatment on the gradient composite plated conductor to obtain a copper-based alloy sliding contact conductor with multi-component composite plating on the surface.

2. The method according to claim 1, characterized in that, The metal transition layer is a nickel transition layer that continuously covers the surface of the active copper substrate, and the conductive support layer is a silver conductive support layer that continuously covers the nickel transition layer and does not contain silicon carbide particles or graphite particles. The gradient multi-element composite working layer includes a first composite layer segment, a second composite layer segment, and a third composite layer segment formed sequentially outward from the silver conductive support layer. The silver conductive support layer and the three composite layer segments adopt a continuously grown silver matrix, and the co-deposition level of silicon carbide particles and graphite particles in the three composite layer segments increases progressively in the order of the first composite layer segment, the second composite layer segment, and the third composite layer segment.

3. The method according to claim 2, characterized in that, After the first composite layer segment is formed and the second composite layer segment is formed, a non-contact airflow is formed by using clean, oil-free gas to act laterally on the working surface to remove the composite plating solution carried on the surface of the corresponding composite layer segment that can flow or drip. The detached composite plating solution is returned to the corresponding original composite plating solution tank, and a continuous wet liquid film is retained on the surface of the corresponding composite layer segment.

4. The method according to claim 1, characterized in that, The respective mass ratio of silicon carbide particles and graphite particles is characterized by the mass concentration of the corresponding particles in the corresponding composite plating solution; let the mass concentrations of silicon carbide particles in the first, second, and third composite plating solutions be respectively... , and The mass concentrations of graphite particles added were as follows: , and Particle size distribution gradient coefficient for: ; The particle ratio gradient coefficient It ranges from 1.9 to 2.

4.

5. The method according to claim 4, characterized in that, The first composite plating solution contains 3.0 g / L silicon carbide particles and 1.0 g / L graphite particles; the second composite plating solution contains 5.7-7.2 g / L silicon carbide particles and 1.9-2.4 g / L graphite particles; the third composite plating solution contains 10.8-17.3 g / L silicon carbide particles and 3.6-5.8 g / L graphite particles. The particle concentrations in the second and third composite plating solutions are determined according to the same particle ratio gradient coefficient K, and the mass ratio of silicon carbide particles to graphite particles in all three composite plating solutions is 3:

1.

6. The method according to claim 1, characterized in that, The first, second, and third composite plating solutions are respectively set in independent composite plating tanks, and are respectively output from and returned to the original composite plating tank through independent circulation pipelines. All three composite plating solutions use non-cyanide sulfite-based silver plating solutions. The silver ion concentration, free sulfite concentration, and pH in the three composite plating solutions are all set with the same target values. Specifically, the silver ion concentration is 20-40 g / L, the free sulfite concentration is 80-160 g / L, and the pH is 8.0-9.

5. The independent circulation pipelines are not equipped with fine filtration components to intercept silicon carbide particles and graphite particles.

7. The method according to claim 6, characterized in that, The silicon carbide particles have an average particle size of 0.3-1.5 μm, and the graphite particles have an average particle size of 0.5-2.0 μm. The silicon carbide particles and the graphite particles are respectively added to their respective aqueous dispersion media, and a nonionic dispersant is added at a dosage of 0.5%-2.0% of the corresponding particle mass. The media are then subjected to mechanical stirring and ultrasonic dispersion for 15-40 min to form a silicon carbide particle dispersion with a particle mass concentration of 80-150 g / L and a graphite particle dispersion with a particle mass concentration of 50-100 g / L. The corresponding base silver plating solution is kept circulating, and the silicon carbide particle dispersion is sent to the mixing zone of the circulating plating solution. After circulating and mixing, the graphite particle dispersion is then sent to the mixing zone.

8. The method according to claim 2, characterized in that, The thickness of the first composite layer segment accounts for 25%-40% of the total thickness of the gradient multi-element composite working layer, the thickness of the second composite layer segment accounts for 30%-40% of the total thickness of the gradient multi-element composite working layer, and the thickness of the third composite layer segment accounts for 25%-40% of the total thickness of the gradient multi-element composite working layer. The sum of the thickness ratios of the three composite layer segments is 100%, and the total thickness of the gradient multi-element composite working layer is 10-25 μm. The plating temperature for forming the three composite layer segments is 25-40℃, and the cathode current density is 0.5-2.0 A / dm. 2 Furthermore, the silver ion concentration, free sulfite concentration, pH, and plating temperature in the three composite plating stages all adopted the same target values.

9. The method according to claim 2, characterized in that, Nickel electrodeposition was performed on the kept-moistened active copper-based surface using a nickel plating bath with a nickel ion concentration of 50-100 g / L, a pH of 3.5-4.8, a temperature of 40-60 °C, and a cathode current density of 1.0-4.0 A / dm³. 2 A nickel transition layer with a thickness of 0.5-2.0 μm is formed. Silver electrodeposition is performed on the surface of the nickel transition layer using a non-cyanide sulfite silver electroplating system. The silver plating bath has a silver ion concentration of 20-40 g / L, a free sulfite concentration of 80-160 g / L, a pH of 8.0-9.5, a temperature of 25-40 °C, and a cathode current density of 0.5-2.0 A / dm³. 2 This forms the silver conductive support layer with a thickness of 3-8 μm.

10. The method according to claim 9, characterized in that, The pretreatment before plating is carried out in the following order: degreasing, water washing, micro-etching, water washing, and activation. Specifically, the working surface is continuously degreased for 1-5 minutes using an alkaline degreasing solution at 40-65℃. The washed working surface is then continuously micro-etched using a sulfuric acid-hydrogen peroxide micro-etching system. The sulfuric acid concentration in this system is 50-120 g / L, the hydrogen peroxide concentration is 15-40 g / L, the micro-etching temperature is 20-35℃, the micro-etching time is 20-90 s, and the micro-etching depth is 0.3-1.5 μm. The micro-etched and washed working surface is then activated using a sulfuric acid aqueous solution with a concentration of 30-80 g / L at 15-30℃ for 15-60 s. After activation, the activated solution carried on the working surface is replaced with flowing water to keep the activated copper-based surface continuously moist.